2007
DOI: 10.1073/pnas.0609301103
|View full text |Cite
|
Sign up to set email alerts
|

Differential fitness costs of reproduction between the sexes

Abstract: Natural selection does not necessarily favor maximal reproduction because reproduction imposes fitness costs, reducing parental survival, and offspring quality. Here, we show that parents in a preindustrial population in North America incurred fitness costs from reproduction, and women incurred greater costs than men. We examined the survivorship and reproductive success (Darwinian fitness) of 21,684 couples married between 1860 and 1895 identified in the Utah Population Database. We found that increasing numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
120
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 55 publications
6
120
1
2
Order By: Relevance
“…While women often experience higher physiological and parenting costs to reproduction, men pay reproductive costs in terms of acquiring and keeping mates, and may also engage in parenting. The last is associated with slight mortality increases after parenthood [32]. As further evidence that these are significant costs, it is worth noting that age-specific mortality is higher for males than females, and particularly higher for young men in part because they engage in high-risk forms of intra-sexual competition [41].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…While women often experience higher physiological and parenting costs to reproduction, men pay reproductive costs in terms of acquiring and keeping mates, and may also engage in parenting. The last is associated with slight mortality increases after parenthood [32]. As further evidence that these are significant costs, it is worth noting that age-specific mortality is higher for males than females, and particularly higher for young men in part because they engage in high-risk forms of intra-sexual competition [41].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have argued that a man should favour larger families because the cost of producing each offspring is lower for him than for a woman [10,32]. However, differential costs do not mean that men and women necessarily have different optimal fertility strategies (but see the electronic supplementary material for how it can affect sexual conflicts of interest).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that under unfavourable environmental conditions, such fitness costs of reproduction may be more pronounced (Reznick 1985;. Unfavourable conditions might originate from high density ( FestaBianchet et al 1998), a high level of aggressive interactions (Lindströ m 2001), low food availability (Davis et al 2005;Penn & Smith 2007) or harsh weather ( Tavecchia et al 2005).…”
Section: Introductionmentioning
confidence: 99%